College Sport Publication Trends Over 15 Decades: A Bibliometric Analysis - Davi Sofyan; Khairul Hafezad Abdullah (Program Studi Ilmu Perpustakaan UIN Alauddin, 2022)
College sports have a significant impact on sport development. This study aims to provide a comprehensive elaboration by describing the publication's descriptive parameters, visualizing the citation pattern, extracting the author's keywords, and determining the impact and performance of research on college sports. This study includes an orientation for researchers to better understand advances in collegiate sports-related scientific publications. A thorough examination of the 947 documents found in the Scopus database was conducted from 1869 to 2022. According to the findings, the number of publications fluctuated, with 2021 having the highest number of publications. Among the 49 other countries, scholars from China accounted for approximately 325 of total global publications. Furthermore, with a total of 55 documents, the Journal of Medicine and Science in Sports and Exercise is one of the most productive scientific sources. Overall, this topic's research is evolving, with new methods and directions being established. As a result, an in-depth examination of collegiate sports in a variety of research areas can help researchers and practitioners advance prospective knowledge in these fields.